Eponychial lesions following bilateral upper extremity vascular composite allotransplantation: a case report. Issue 1 (1st January 2018) - Fallahian, Fedra; Molway, David; Jadeja, Saagar; Clark, Rachael; Marty, Francisco M.; Riella, Leonardo V.; Chandraker, Anil; Talbot, Simon G.
Abstract: Vascularized composite allotransplantation represents a useful addition to reconstructive options available to the plastic surgeon. Though the procedure provides beneficial functional outcomes, there remain complications, often associated with the immunosuppression necessary to maintain an allograft. We report a case of eponychial fold lesions following successful bilateral upper extremity allotransplantation.